Technical issues and engagement processes: support for citizen and expert deliberation regarding the management of nuclear waste - Reedy, Justin; Anderson, Chris; Nowlin, Matthew C. (Frontiers in Communication, 2023)
Deliberative forums have been increasingly used to involve citizens in policymaking, but it is unclear whether people trust their fellow citizens to make decisions in highly technical areas like nuclear policy relative to more commonly used expert bodies. We examine public support for citizen and expert deliberation regarding the siting of nuclear waste facilities and note the role of values, views on deliberation, and civic experiences on support for each type of deliberation. We find that past civic experiences are associated with increased support for citizen decisionmaking. In addition, we find that underlying views on nuclear power may be more important in shaping support for a decision on nuclear waste facility siting than attitudes toward particular kinds of governance processes.